Pendidikan Kesehatan Metode Demonstrasi dan Ceramah Meningkatkan Kemampuan Latihan Batuk Efektif pada Anak Usia Sekolah - Syahtya Dzulandita Magfiroh; Ninuk Dian Kurnawati; Kristiawati Kristiawati (Universitas Airlangga, 2019)
Introduction: Cough is one of clinical manifestations of respiratory tract infection. Technique of effective cough helps remove pleghm more easily during cough. However, the optimum implementation of effective cough has not been performed well. Changing the behavior of practicing effective cough to students needs a lot effort. One of it is by giving health education using the demonstration and lecture. The aimed of this study was to analyze the effectiveness of health education the knowledge, attitudes and actions of practicing effective cough between the demonstration method and lecture to students. Method: A quasy experiment research design was used in this study. The sample was students of SDN Grogol Sidoarjo and there were 44 students. Purposive sampling was used in this study. Data were obtained using questionnaires and standard operational procedures.Result: The effectiveness of health education between the demonstration used and lecture were analyzed using Mann Whitney U Test. The results showed that demonstration and lecture were effective to change knowledge, attitudes and actions of students with p=0.004, p=0.003, and p=0.003 respectively. Discussion: The author concluded that the demonstrations and lecture can enhance the ability to perform effective cough practice. However, the demonstration is more effective to be applied to students in order to improve their ability to practice effective cough because demonstration directly exhibit something that’s followed by students in order to the knowledge or skill is easier to br memorized.